Molecular cloning and expression of an additional epidermal growth factor receptor-related gene. - Plowman, G D (1990)
Epidermal growth factor (EGF), transforming growth factor alpha (TGF-alpha), and amphiregulin are structurally and functionally related growth regulatory proteins. These secreted polypeptides all bind to the 170-kDa cell-surface EGF receptor, activating its intrinsic kinase activity. However, amphiregulin exhibits different activities than EGF and TGF-alpha in a number of biological assays. Amphiregulin only partially competes with EGF for binding EGF receptor, and amphiregulin does not induce anchorage-independent growth of normal rat kidney cells (NRK) in the presence of TGF-beta. Amphiregulin also appears to abrogate the stimulatory effect of TGF-alpha on the growth of several aggressive epithelial carcinomas that overexpress EGF receptor. These findings suggest that amphiregulin may interact with a separate receptor in certain cell types. Here we report the cloning of another member of the human EGF receptor (HER) family of receptor tyrosine kinases, which we have named "HER3/ERRB3." The cDNA was isolated from a human carcinoma cell line, and its 6-kilobase transcript was identified in various human tissues. We have generated peptide-specific antisera that recognizes the 160-kDa HER3 protein when transiently expressed in COS cells. These reagents will allow us to determine whether HER3 binds amphiregulin or other growth regulatory proteins and what role HER3 protein plays in the regulation of cell growth.